Some Recent American Progress In The Assay Of Copper-Bullion. - Edward Keller (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1913)
THE ASSAY FOR COPPER. SOMEONE some time ago remarked that some chemists still insist on telling us how to determine copper by the electrolytic method. The. writer must confess that he believes that everything is not known definitely as yet as to how the exact amount of copper is determined in such material as purest commercial electrolytic copper. Some of us are not yet convinced that the pure copper atom is at all times deposited from an acid solution and that no oxygen or hydrogen will, under certain conditions, accompany it. Difficulties with impurer material are frequent, but erroneous results are not always apparent, since these do not speak so readily for themselves as those in the first case. By this is meant that if a chemist finds 100 per cent. of copper in electrolytic copper it is pretty certain that he perceives the result to be wrong, while if he finds 0.1 per cent. of copper too much in a very impure material he is far more likely to be unconscious of his error. These, in a wide experience, are frequent happenings and the writer has always looked with interest to publications on this subject. In turn, he :feels justified in giving to others a few of his own observations. Up to a few years ago there were two methods of electrolytic copper assay in technical use, which had in common, that the amount of copper deposited on the cathode did not exceed 2 g., and they differed in that, for the one a large sample 1 (20 to 80 g.) was taken from the general sample by a splitting device, dissolved, and from the solution a small portion (to contain 1 or 2, g. of copper) measured out for the electrolytic deposition; in the other Method the copper was determined, generally in 1-g. portions of the separated coarse and fine portions of the sample, all of which passed -a 16 or 20-mesh screen, being accomplished by a 40-mesh screen,